Pure yeast beta-glucan and two types of yeast cell wall extracts enhance cell migration in porcine intestine model. (August 2019) - Penney, Jenna; Lu, Yang; Pan, Bo; Feng, Yulong; Walk, Carrie; Li, Julang
Graphical abstract: Highlights: Pure β-glucans and yeast cell walls containing β-glucans enhanced cell migration through the ELK1 pathway. Β-glucans in purified form and from yeast cell walls activated CD22 receptors to reduce inflammation. Processing, which changed the cell wall structure, had an influence on the cytotoxicity of the yeast cell wall. Pure β-glucans and hydrolyzed yeast cell wall responses were similar when compared with autolyzed yeast cell walls. Abstract: Beta-Glucans are commonly used health supplements for humans and animals. They represent a promising avenue to help combat many widespread health concerns including intestinal upset and inflammation. These beneficial effects may be different from species to species and between different cell types and therefore it is important to examine the mechanisms in any species or cell type for which this supplement may be used in. In this study we have shown that pure Beta-Glucans and the less processed yeast cell wall extracts significantly enhance cell migration in a porcine intestinal cell model, potentially through activation of the ELK1 pathway. The expression of migration-related genes was also seen to be significantly increased in response to Beta-Glucan treatment. Our data suggests that Beta-Glucans activate the CD22 receptor in the pig intestine, which has the potential to reduce inflammation. Overall, we found a novel mechanism through which Beta-Glucans exert their effects in the pig intestinal cell model.